Anti-Maxwell Land Grant Compony meeting in Cimarron 1880
Anti-Maxwell Land Grant Company meeting was held in Cimarron in 1880. O. P. Maines circled William F. M. Army with long white hair in foreground.
Black and White photographs - From the collection of Alper's Family
Master list item #: 30
File location is in the Raton file Cabinet
Keywords: Army, William F. M; Anti-Maxwell Land Grant Company; Male Photographs; Historic Photographs; Family Photographs; Cimarron, New Mexico